(untitled) (Biological Sciences - PJSIR, 2006)
. The presence of clay deposits in the south-southern part of Nigeria was investigated using the electrical resistivity method. The vertical electrical sounding was adopted for the investigation using the Schlumberger electrode arrangement. Resistivity soundings were collected from several locations, which were evenly distributed within the study area to explore the clay deposits. Models were generated for computer iterative technique. Borehole data were also collected using spontaneous potential logging method, as well as driller’s log in some selected sites within the study area, so as to correlate surface measurements with borehole records. Analysis based on five depth-related resistivity contour maps, as well as selected cross-sectional profiles, confirm the existing dual regional geological environment of the area. Finally, it was established quantitatively that there were comparatively larger clay mineral deposits in the sedimentary environment than in the basement complex areas.